Two new species of Theloderma (Anura: Rhacophoridae) from Vietnam - Rowley, Jodi J. L.; Le, Duong Thi Thuy; Hoang, Huy Duc; Dau, Vinh Quang; Cao, Trung Tien (Zootaxa, 2011)
Two new species of rhacophorid frogs in the genus Theloderma are described from high-elevation montane forest on the Kon Tum and Langbian Plateaus in Vietnam, on the basis of morphological and molecular evidence. Both new species are differentiated morphologically from their congeners by their small body size (Theloderma, and are distinct from all congeners sampled (uncorrected sequence divergences at the 16S rRNA gene of >8.5% for all Theloderma for which homologous 16S rRNA sequences are available). The new species are differentiated from each other by dorsal pattern, extent of dorsal asperities, and by mitochondrial DNA.